The effects of occupational stress on the management of an organization - Azizi Yahaya; Ismail Maakip; Peter Voo Su Kiong; Sharon Kwan Sam Mee; Joki Perdani Sawai (AESS Publications, 2019)
Occupational stress is an important issue not only for the researchers but also for the employees and managers at work. This study aims to determine the effects of occupational stress on job satisfaction, intention to leave and absenteeism. A sample of 100 employees in the Companies Commission of Malaysia, a statutory body regulating companies and businesses was recruited to participate in the study. A questionnaire was used to collect information on demographics, stress, job satisfaction, intention to leave and absenteeism. Pearson correlation and Multiple Linear Regression was used to examine the relationships between different variables. The results show that occupational stress does not have a direct effect on the intention to leave and absenteeism. In contrast, occupational stress has a direct negative effect on job satisfaction. Furthermore, job satisfaction has negative effects on the intention to leave and absenteeism. In conclusion, the authors recommend the following to management: (a) increasing job satisfaction by reducing employee occupational stress, and (b) that by reducing stress, the organization can reduce the levels of intention to leave and absenteeism among employees